Hubungan Tingkat Pengetahuan Dengan Kejadian Anemia Pada Remaja Putri Di Wilayah Kerja Klinik - Siamputri , Indri; Septiyana, Ria; Damayanti , Ferina (Jurnal Farmasi Sains dan Teknologi, 2025)
Anemia is one of the common health problems in Indonesia; regardless of age and gender, anemia can be suffered by anyone without realizing it. This study is quantitative. The study was conducted from March to May 2025, and the sampling technique used was the total sampling method. The results of the study showed that, based on age, the majority of respondents have an age range of 13-17 years, with the highest percentage of 43.6%. The level of education can be seen that respondents with the highest level of education, high school, have the highest percentage of 54.4%. The level of knowledge is sufficient for as many as 37 respondents (67.3%).